ANALYSIS OF MORAL VALUES IN TERE LIYE’S NOVEL “PULANG” - Dielarenza Destelita Wahana Putri; Marudut Bernadtua Simanjuntak (Badan Penerbit STIEPARI Press, 2022)
Literary works are creations of aesthetic values that the author wants to communicate through writing, such as telling a story in the first person or in the third person. The literary novel